Evaluation of Olive Preservation Methods on Bioactive Constituents and Antioxidant Properties of Olive Oils. (16th March 2017) - Irmak, Şahnur; Kadiroğlu, Pınar; Ötleş, Semih
Abstract: The purpose of this study was to determine the effects of preservation methods on less salty natural black table olives by evaluating the extracted olive oils. For this purpose, olives of the Gemlik variety obtained in two harvest years were brined and dry salted with 2 and 4% levels of salt and packaged with vacuum and modified atmosphere (60% N2 and 40% CO2 ) and treated with gamma irradiation (0, 1, 3, 5 kGy). The olive oil extraction process was applied to raw olives, olives after fermentation and olives at 4th and 8th months of storage time. Bioactive component analyses including total carotenoid, total chlorophyll, α‐tocopherol analyses and antioxidant properties were performed along with determination of free fatty acids content (FFA) and peroxide values (PV). FFA and PV increased while α‐tocopherol (TO), total chlorophyll (TCH), total carotenoids (TC) and antioxidant activity (DPPH· radical scavenging assay) values decreased with storage and increment of irradiation dosage. Principal components analyses (PCA) showed that olive oils were discriminated clearly according to harvest year, salt content and processing type (dry‐salting and brining). Overall, this study revealed that chemical parameters of olive oils as the main component of the olives were affected by the harvest year, processing and preservation conditions along with fermentation and storage period of olives.